HIV and AIDS Updates on Biology, Immunology, Epidemiology and Treatment Strategies - Dumais, Nancy (IntechOpen, 2011)
The continuing AIDS pandemic reminds us that despite the unrelenting quest for knowledge since the early 1980s, we have much to learn about HIV and AIDS. This terrible syndrome represents one of the greatest challenges for science and medicine. The purpose of this book is to aid clinicians, provide a source of inspiration for researchers, and serve as a guide for graduate students in their continued search for a cure of HIV. The first part of this book, "From the laboratory to the clinic," and the second part, "From the clinic to the patients," represent the unique but intertwined mission of this work: to provide basic and clinical knowledge on HIV/AIDS.